Produção de nanomateriais a base de carbono obtidos a partir da decomposição catalítica de metano - Silva, Juliana Alves da (Universidade Federal de São Carlos, 2022)
The natural gas reforming routes are consolidated technologies in the production of H2, however, these routes produce significant amounts of greenhouse gases and require the separation and purification of H2. The catalytic decomposition of methane (CDM) process is a promising alternative to traditional processes, as it produces COx-free H2 and carbon nanoparticles (nanotubes, carbon nanofibers or graphene-based structures) with wide applicability. To increase the competitiveness of CDM, it is necessary that the carbon produced has a high commercial value. Thus, the quality control of carbon characteristics is essential, as it is expected that carbon nanostructures free of defects and with uniform characteristics have remarkable mechanical, electronic and magnetic properties. However, the quality control of these carbon nanostructured materials is still very low by this process due to several factors that influence their production. To prepare high quality carbon nanotubes or nanofibers and, at the same time, produce H2 with a high yield, it is necessary to develop active and stable catalysts. In the present research project, catalysts based on Ni and Fe were prepared by the coprecipitation, impregnation and fusion method and tested in the decomposition of CH4. The materials were characterized by X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), N2 physisorption, temperature programmed reduction (TPR), Mössbauer spectroscopy, thermogravimetric analysis, transmission and scanning electron microscopy (TEM and SEM). The synthesis method influenced the metal-support interaction, particle size and specific surface area. The catalysts prepared by the coprecipitation and fusion method were more active during the reaction producing fishbone and bamboo carbon nanofibers on Ni and Fe catalysts, respectively. The impregnation method was inefficient in generating nanofibers, promoting the formation of short and irregular fibers. Carbon production was up to 11.8 grams of carbon per gram of iron and 1.4 grams of carbon per gram of nickel for materials prepared by the coprecipitation method. Subsequently, the functionalization of the catalysts used was performed and it was observed that there was an increase in the amount of oxygenated functional groups on the carbon surface, which expands the application and use of these materials.
Production of carbon-based nanomaterials obtained from the catalytic decomposition of methane
Keywords: Decomposição catalítica do metano; Nanofibra de carbono; Catalisadores de Ni-Al e Fe-Al; Catalytic decomposition of methane; Carbon nanofiber; Ni-Al and Fe-Al catalysts; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA